2003
DOI: 10.1073/pnas.1433065100
|View full text |Cite
|
Sign up to set email alerts
|

The double bromodomain protein Brd4 binds to acetylated chromatin during interphase and mitosis

Abstract: Previous in vitro studies showed that the bromodomain binds to acetyllysines on histone tails, leading to the proposal that the domain is involved in deciphering the histone code. However, there is little in vivo evidence supporting the binding of bromodomains to acetylated chromatin in the native environment. Brd4 is a member of the BET family that carries two bromodomains. It associates with mitotic chromosomes, a feature characteristic of the family. Here, we studied the interaction of Brd4 with chromatin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
611
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 599 publications
(650 citation statements)
references
References 51 publications
36
611
3
Order By: Relevance
“…There are four proteins in this subfamily, BRD2 [45], BRD3 [45], BRD4 [46] and BRDT [39]. Interestingly BET proteins are recruited to transcriptional start sites during mitosis [37,47,48] and the BET protein BRD4 has been shown to tether the positive transcription elongation factor (P-TEFb) to these sites via its unique C-terminus. As such, their interactions with histones have been studied in detail by several groups (Table 2).…”
Section: Bromodomain Substratesmentioning
confidence: 99%
“…There are four proteins in this subfamily, BRD2 [45], BRD3 [45], BRD4 [46] and BRDT [39]. Interestingly BET proteins are recruited to transcriptional start sites during mitosis [37,47,48] and the BET protein BRD4 has been shown to tether the positive transcription elongation factor (P-TEFb) to these sites via its unique C-terminus. As such, their interactions with histones have been studied in detail by several groups (Table 2).…”
Section: Bromodomain Substratesmentioning
confidence: 99%
“…Necdin (Ndn) is an imprinted transcription factor on chromosome 7 that has previously been implicated in cellular proliferation, collagen gene expression [25], and regulation of the metastasis-associated gene Hif1a [26,27]. Brd4, on chromosome 17, is a bromodomain-containing protein that associates with chromatin [17]. Intriguingly, Brd4 has been demonstrated to be binding partner of our recently described metastasis efficiency modifier, Sipa1 [16].…”
Section: Identification Of Ecm Eqtl Candidate Genesmentioning
confidence: 99%
“…This methodology not only allowed us to identify Rrp1b as a dual ECM and metastasis efficiency modifier, but also to demonstrate that the cell growth regulator Bromodomain 4 (Brd4) [15][16][17], which also binds Sipa1, has similar properties with regards to metastasis and ECM gene expression (Bromodomain 4 activation predicts breast cancer survival; N.Crawford, J.Alsarraj, L.Lukes, R.Walker, H.Yang, M.Lee, K. Ozato, K.Hunter; PNAS, in press). Furthermore, we demonstrated that differential activity of BRD4 in primary breast cancers accurately predicts outcome in five different tumor gene expression datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Integrated functions in histone interactions have also been shown for tandem modules of the same fold, such as the double bromodomain in human transcriptional proteins BRD2 and BRD4 (ref. 20,21) and Rsc4 of the yeast RSC remodeling complex 22 , the double chromodomain of Drosophila melanogaster CHD1 (chromo-ATPase/helicase-DNA binding) 23 and the double Tudor domain of JMJD2A 24 . However, although tandem modules of different structural folds such as the PHD finger and the bromodomain are found in many transcriptional proteins 25,26 , molecular mechanisms for their possible interactive functions are much less understood.…”
mentioning
confidence: 99%